2003
DOI: 10.1029/2002jc001410
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and circulation on the population dynamics of Calanus finmarchicus in the Gulf of St. Lawrence and Scotian Shelf: Study with a coupled, three‐dimensional hydrodynamic, stage‐based life history model

Abstract: [1] We developed a physical-biological model for the Gulf of St. Lawrence (GSL) and Scotian Shelf (SS) by coupling a stage-based life-history model of the planktonic copepod Calanus finmarchicus to a three-dimensional ocean circulation model. The life-history model consists of 13 morphologically distinct life stages of C. finmarchicus, with stagespecific and temperature-dependent molting rates. The model also includes stage-specific vertical distribution and seasonally varying diapause, egg production, and sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 93 publications
1
39
0
3
Order By: Relevance
“…The behavioural model of Fiksen (2000) cues diapause entry in a similar way to Carlotti & Wolf (1998), but only during the C5 stage. Tittensor et al (2003) allow individuals to enter diapause at a constant rate throughout the C5 stage, while Zakardjian et al (2003) had a similar approach but with a seasonally varying rate. It has also been suggested that the arrival of seasonally migrating fish can promote diapause entry (Kaartvedt 2000), although the difficulties of representing predator fields means this has never been included in a demographic model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The behavioural model of Fiksen (2000) cues diapause entry in a similar way to Carlotti & Wolf (1998), but only during the C5 stage. Tittensor et al (2003) allow individuals to enter diapause at a constant rate throughout the C5 stage, while Zakardjian et al (2003) had a similar approach but with a seasonally varying rate. It has also been suggested that the arrival of seasonally migrating fish can promote diapause entry (Kaartvedt 2000), although the difficulties of representing predator fields means this has never been included in a demographic model.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a number of authors have used Eulerian descriptions of Calanus finmarchicus in which the spatial domain is divided up into set of discrete cells (Bryant et al 1997, Tittensor et al 2003, Zakardjian et al 2003. These models are a more natural representation of the density of organisms continuously distributed over large areas, but the accurate characterization of both spatial and physiological structure by standard methods is computationally demanding.…”
Section: Introductionmentioning
confidence: 99%
“…However, the necessary observations and understanding of depth selection and foraging behavior in marine zooplankton are extremely limited. Thus, for example, modeling studies of mesozooplankton population dynamics embedded in multidimensional ocean circulation schemes repeatedly identify controls of vertical distribution and migration behavior (that is, depth selection) by individual zooplankters as essential information that is usually unknown (Batchelder et al 2002;Hannah et al 1997;Miller et al 1998;Reiss et al 2003;Werner et al 1993;Wroblewski 1982;Zakardjian et al 2003). Recent modeling work suggests that small-scale behaviors such as foraging may indeed have a large impact on the transport of zooplankters (Woodson and McManus 2007).…”
Section: Introductionmentioning
confidence: 99%
“…C'est dans ce contexte écosystémique que s'inscrivent les processus responsables de l'existence et des variabilités spatiale et temporelle du site d'alimentation traditionnel des baleines du PMSSL (Figure 2). Le « bloom » printanier (prolifération massive du phytoplancton) qui démarre immédiatement après la fonte des glaces en avril dans le golfe du Saint-Laurent, en exploitant les éléments nutritifs remis en disponibilité dans la couche photique par le profond mélange vertical encouru depuis l'automne précédent, initie la ponte des espèces zooplanctoniques herbivores dominantes de copépodes et d'euphausides (krill) ayant complété leur diapause (baisse de l'intensité des activités métaboliques) hivernale (DE LAFONTAINE et al, 1991;LE FOUEST et al, 2005;MAUCHLINE, 1980;PLOURDE et RUNGE, 1993;PLOURDE et al, 2001;PLOURDE et THERRIAULT, 2004;ZAKARDJIAN et al, 2003). Ceci amorce le processus de production biologique conduisant à la formation des agrégations de zooplancton et, éventuellement, de leurs prédateurs, poissons pélagiques ou baleines planctivores et piscivores (DE LAFONTAINE et al, 1991;PLOURDE et al, 2001;RUNGE et SIMARD 1990;RUNGE et al, 1999;THERRIAULT, 1991).…”
Section: L'écosystème à Grande éChelle Du Pmsslunclassified